Bis- and mono-tridentate chelated iron complexes with a new facially capping unsymmetrical nitrogen ligand: X-ray structural and spectroscopic studies. (15th January 2019) - Chetty, Nisha; Ramkumar, V.; Murthy, Narasimha N.
Graphical abstract: Two new bis- and mono-tridentate chelated iron complexes, [Fe II (L H )2 ](ClO4 )2 ·C2 H5 OH (1 ) and [Fe III (L H )Cl3 ]·0.5CH2 Cl2 (2 ), with facially capping N-tridentate ligand, 2-(5, 7-dihydro-6H-dibenzo[c, e]azepin-6-yl)-N-(pyridin-2-ylmethyl)ethan-1-amine, incorporating biphenyl-append (L H ), have been synthesized and characterized by X-ray crystal structure, spectroscopic (FTIR, UV–Vis and ESI-MS) and magnetic susceptibility measurements. Crystal structures of1 and2 reveal pseudo-octahedral geometry with two ligand (L H ) molecules arranged in trans-facial manner and similar geometry with one facially capping ligand, L H and three Cl −, respectively. Their characterizations in solution by spectroscopic (FTIR, UV–Vis and ESI-MS) methods and a qualitative variable temperature (20–300 K) magnetic susceptibility (VSM) of solids complement solid state structures. Abstract: Two new bis- and mono-tridentate chelated iron complexes, [Fe II (L H )2 ](ClO4 )2 ·C2 H5 OH (1 ) and [Fe III (L H )Cl3 ]·0.5CH2 Cl2 (2), with facially capping N-tridentate ligand, 2-(5, 7-dihydro-6H-dibenzo[c, e]azepin-6-yl)-N-(pyridin-2-ylmethyl)ethan-1-amine, incorporating biphenyl-append (L H ), have been synthesized and characterized by X-ray crystal structure, spectroscopic (FTIR, UV–Vis and ESI-MS) and magnetic susceptibility measurements. Structure of1 reveals pseudo-octahedral geometry around Fe(II) with two ligands (L H ) arranged in trans-facial manner, in two crystallographic independent molecules, Mol. A and Mol. B, differing in biphenyl twist angles, ϕ  = 43.7° and 45.1°. Complex2 has similar geometry with Fe(III) having one facially capping ligand, L H and three chlorides (Cl − ), also in two crystallographic independent molecules, Mol. A and Mol. B, differing by biphenyl twist angles, ϕ  = 40.9° and −42.7°. The UV–Vis absorption spectrum of2 in CH3 CN suggests competitive coordination between the two weakly-coordinating tertiary amine nitrogen atoms having biphenyl-append, and the solvent, CH3 CN. The qualitative magnetic susceptibility measurements for1 and2 at 296 K provide moments of 4.2 μB and 2.7 μB, respectively, suggesting nearly high-spin, Fe(II) ( S  = 2) and a rare intermediate-spin, Fe(III) ( S  = 3/2).